Effects of Fmr1 Gene Mutations on Sex Differences in Autism-Like Behavior and Dendritic Spine Development in Mice and Transcriptomic Studies - Wang, Zhao; Qiao, Dan; Chen, Huan; Zhang, Shihua; Zhang, Bohan; Zhang, Jingbao; Hu, Xiangting; Wang, Chang; Cui, Huixian; Wang, Xia; Li, Sha (Neuroscience, 2023)
•Fmr1 KO mice display sex differences in autism-like behavior and dendritic spine.•Male mice have more severe effects in autism-like behavior and dendritic spine.•There is sex-biased mRNA expression in the hippocampus of Fmr1 KO mice.•Differential gene expression affects the behavior of Fmr1 KO male and female mice.•Studies should incorporate females to reflect the different of FXS in both sexes. Fragile X syndrome (FXS) is the most common single gene disorder contributing to autism spectrum disorder (ASD). Although significant sex differences are observed in FXS, few studies have focused on the phenotypic characteristics as well as the differences in brain pathological changes and gene expression in FXS by sex. Therefore, we analyzed sex differences in autism-like behavior and dendritic spine development in two-month-old male and female Fmr1 KO and C57 mice and evaluated the mechanisms at transcriptome level. Results suggest that Fmr1 KO mice display sex differences in autism-like behavior and dendritic spine density. Compared to females, male had more severe effects on anxiety, repetitive stereotype-like behaviors, and socializing, with higher dendritic spine density. Furthermore, two male-biased and five female-biased expressed genes were screened based on KEGG pathway enrichment and protein–protein interaction (PPI) analyses. In conclusion, our findings show mutations in the Fmr1 gene lead to aberrant expression of related genes and affect the sex-differentiated behavioral phenotypes of Fmr1 KO mice by affecting brain development and functional architecture, and suggest future studies should focus on including female subjects to comprehensively reflect the differentiation of FXS in both sexes and develop more precise and effective therapeutic strategies.